2018
DOI: 10.1007/s00018-018-2982-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular transport and regulation of transcytosis across the blood–brain barrier

Abstract: The blood–brain barrier is a dynamic multicellular interface that regulates the transport of molecules between the blood circulation and the brain parenchyma. Proteins and peptides required for brain homeostasis cross the blood–brain barrier via transcellular transport, but the mechanisms that control this pathway are not well characterized. Here, we highlight recent studies on intracellular transport and transcytosis across the blood–brain barrier. Endothelial cells at the blood–brain barrier possess an intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 123 publications
(151 reference statements)
3
115
0
Order By: Relevance
“…Lipid transport and lipid mediators, including ASM, regulate the assembly of caveolae, which are involved in transcytosis across the BBB, at plasma membranes in brain ECs 52,53 . Caveolae are submicroscopic vesicles that are associated with the plasma membrane and consist of caveolin-1 (Cav-1) membrane proteins and cytoplasmic cavin proteins [54][55][56] .…”
Section: Asm In Aged Brainmentioning
confidence: 99%
“…Lipid transport and lipid mediators, including ASM, regulate the assembly of caveolae, which are involved in transcytosis across the BBB, at plasma membranes in brain ECs 52,53 . Caveolae are submicroscopic vesicles that are associated with the plasma membrane and consist of caveolin-1 (Cav-1) membrane proteins and cytoplasmic cavin proteins [54][55][56] .…”
Section: Asm In Aged Brainmentioning
confidence: 99%
“…Nanoparticle delivery to the brain has gathered special interest for the diagnosis and treatment of neurodegenerative diseases, cancer and other brain-derived pathologies. However, unlike the endothelial barriers between the blood and other tissues, transport across the BBB is much more regulated and poses an additional constraint for targeting neural tissues [ 231 ]. Although disease conditions are known to increase BBB permeability, diagnostic and therapeutic strategies are ideally performed at early stages before BBB disruption [ 231 ].…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
“…However, unlike the endothelial barriers between the blood and other tissues, transport across the BBB is much more regulated and poses an additional constraint for targeting neural tissues [ 231 ]. Although disease conditions are known to increase BBB permeability, diagnostic and therapeutic strategies are ideally performed at early stages before BBB disruption [ 231 ]. Therefore, nanoparticles should be able to cross healthy barriers.…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to development of cancer therapeutics, at the preclinical level, another intriguing concept is delivery of drugs across the blood brain barrier (BBB) into the brain by using ILPs. The BBB, where cell membrane proteins involved in receptor-mediated transcytosis, such as transferrin receptor and insulin receptor are expressed, is a selective barrier between systemic blood circulation and brain parenchyma [ 105 , 106 , 107 , 108 ]. Recently, Johnsen et al reported that intravenous injection of OX26 (a mouse anti-rat CD71/transferrin receptor monoclonal antibody)-conjugated and oxaliplatin-encapsulated liposome resulted in higher concentration of platinum in the rat brain parenchyma compared to the control ILP [ 109 ].…”
Section: Application Of Functional Monoclonal Antibodies As Immunomentioning
confidence: 99%